If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3X = y Solving 8 + -3X = y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3X = -8 + y Combine like terms: 8 + -8 = 0 0 + -3X = -8 + y -3X = -8 + y Divide each side by '-3'. X = 2.666666667 + -0.3333333333y Simplifying X = 2.666666667 + -0.3333333333y
| 4(2x+9)=-34+54 | | 12c^2+9c^3= | | 30=x+12 | | x+3+2x+5=78 | | -5(4x-2)+21x-20= | | 4x-8y=21 | | 12(x-3)-4x=4 | | 9-2(a-2)=2+a | | 2344-555= | | 3(-6)/5=26-3 | | 5-1/3x=0 | | 2x^2-3x-125=0 | | 9-9sin(8x)=6cos^2(8x) | | x+15-3(x-2)=-11 | | (2y-4)-5y=-13 | | 2+2d=8+d | | -5-5x=35 | | -2(5t-4)+3t=2t-6 | | -5-5=35 | | 5-1/3x0 | | 3(4x-4)-11(x-2)= | | F(x)=-20x+5x^2+9 | | 12x-5+3x=11x-2+3x | | z^4+(2i-3)z^2-6i=0 | | 11+2x=81 | | 2(3X+5)-6=3X-8 | | 5x-28=232 | | F(x)=-7-3x^2+12x | | z^4(2i-3)z^2-6i=0 | | https://youtu.be/LRn | | 3(-6)-5=26-3 | | 7(-9-2x)=-105 |